2008
DOI: 10.1111/j.1442-2042.2008.02155.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological prophylaxis of venous thromboembolism in contemporary radical retropubic prostatectomy: Does concomitant pelvic lymphadenectomy matter?

Abstract: Abstract:The prevention of venous thromboembolism is a major concern in cancer patients undergoing pelvic surgery. Radical retropubic prostatectomy is a common treatment for localized prostate cancer and has been identified as a high risk procedure for postoperative venous thromboembolism. However, most patients diagnosed with prostate cancer in the current era have clinically localized , low volume disease and the risk of venous thromboembolism is very low. Multiple guidelines exist for the prevention of veno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…16 Meanwhile, Benjamin et al suggested that lymphocele was an independent risk factor for VTE, and pharmacological thromboprophylaxis increased the rate of lymphocele formation. 25 Lymphocele was diagnosed in three patients who had undergone prostatectomy with concomitant pelvic lymphadenectomy in the present study. However, there were no VTE events in these cases.…”
Section: Discussionmentioning
confidence: 55%
“…16 Meanwhile, Benjamin et al suggested that lymphocele was an independent risk factor for VTE, and pharmacological thromboprophylaxis increased the rate of lymphocele formation. 25 Lymphocele was diagnosed in three patients who had undergone prostatectomy with concomitant pelvic lymphadenectomy in the present study. However, there were no VTE events in these cases.…”
Section: Discussionmentioning
confidence: 55%
“…Perioperative administration of heparin to prevent deep venous thrombosis has been associated with lymphocele development. [14][15][16] However, a recent study by Naselli et al found no association between the use of heparin prophylaxis and development of lymphoceles. 3 In the present study, patients undergoing LRP routinely received LMWH, starting before surgery and continued daily until discharge, whereas patients undergoing ORP did not routinely receive LMWH, but had sequential compression boots unless there was a history of thromboembolism.…”
Section: Discussionmentioning
confidence: 97%
“…Perioperative administration of heparin to prevent deep venous thrombosis has been associated with lymphocele development 14–16 . However, a recent study by Naselli et al .…”
Section: Discussionmentioning
confidence: 99%
“…142 In the open surgery thromboembolic events could be due to the extra peritoneal approach. 143,144,145 Lymph-node dissection also leads to an increased risk of lymphocele formation, especially after open surgery. 146…”
Section: Complicationsmentioning
confidence: 99%